1967
DOI: 10.1029/jz072i022p05705
|View full text |Cite
|
Sign up to set email alerts
|

Spectral reflectance 0.4 to 2.0 microns of silicate rock powders

Abstract: Silicate rocks in powdered form can be classified as belonging to the broad categories of rock glasses, crystalline acidic rocks, or crystalline basic‐ultrabasic rocks, on the basis of spectral reflectance properties in the 0.4‐ to 2.0‐μ wavelength region. Distinguishing characteristics are the ratio of reflected light at 0.7 μ to that at 0.4 μ, here termed R/B, the change in R/B with albedo, the maximum albedo of a rock powder, and the occurrence of broad absorption bands in the reflectance spectrums between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
87
2

Year Published

1973
1973
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(101 citation statements)
references
References 7 publications
12
87
2
Order By: Relevance
“…In light of the results by Adams and Filice [1967] on albedo variations with changing particle size, this is not surprising. An absolute albedo calibration during the remote-sensing observations would be required in order to apply this class of calibrations.…”
Section: Analytical Groupings and General Trendsmentioning
confidence: 95%
“…In light of the results by Adams and Filice [1967] on albedo variations with changing particle size, this is not surprising. An absolute albedo calibration during the remote-sensing observations would be required in order to apply this class of calibrations.…”
Section: Analytical Groupings and General Trendsmentioning
confidence: 95%
“…We speculate that this signature could be evidence for substantial surface exposure and accumulation of mineral impurities in this region of GrIS. The spectra of most minerals exhibit higher NIR reflectance than bare ice, leading to the potential for a trend toward increased NIR albedo while visible albedo drops with high mineral content (Adams and Filice, 1967;Painter et al, 2003;Bøggild et al, 2010;Casey et al, 2012;Tedesco et al, 2013). The SE GrIS margin shows decreasing NIR albedo and only isolated change in visible wavelengths at the lowest elevations.…”
Section: Impact Of C6 Revision On Scientific Investigation Of Grismentioning
confidence: 99%
“…This is a common property of silicate powders discussed by Adams and Filice (1967), who also found that this trend often reverses at large phase angles (powders becoming bluer with increasing phase). There are indications of this happening in some of our samples at phase angles larger than 700.…”
mentioning
confidence: 92%